Analisa Struktur Atas (Upper Structure) Jembatan Kaburejo Kota Pagar Alam - M.Sang Gumilar; M. Ridho Edrizky (JURNAL ILMIAH BERING'S, 2017)
One means of transportation is a bridge that connects an area due to obstacles or road divides. There are many bridges in the City of Pagar Alam, one of which is in the Kaburejo area, the bridge in this area is less feasible for vehicles because it has a smaller bridge span than the highway. The purpose of this study is to do an upper structure re-design with a 6 m wide bridge and a 15 m long bridge span made with reinforced concrete construction that has a reinforced longitudinal beam which is an integral part of the vehicle floor so that it can meet the maximum traffic capacity. Bridge planning analysis is carried out on the bridge structure which includes the backrest, sidewalk floor, floor plate and main beam.